Pengembangan Media Pembelajaran Pop Up Book Pada Pembelajaran IPS Di Kelas IV SD - elyta apriliani; Ana Nurhasanah; Zerri Rahman Hakim (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
In the learning process in the classroom, students often find it difficult to understand the material being taught because the use of learning media is not optimal. This study aims to develop pop-up book learning media and to determine the feasibility of the developed pop-up book learning media. The type of research used is Research and Development (R&D) with research and development procedures from Borg and Gall. The instrument used was a questionnaire sheet for expert validation and student responses. Based on the data analysis, the material expert's assessment was 95.6% in the "Very Good" category; the linguist's assessment of 87.5% is categorized as "Very Good"; the media expert's assessment of 94.3% is categorized as "Very Good" and the assessment of the response of students in class IV SD Negeri Secang by 99% is categorized as "Very Good". So that the pop-up book meets the criteria to be used as a learning medium.